Research on Agricultural Supply Chain Coordination Considering Financial Constraints Under Blockchain Technology - Lingling Xu; Wenhui Zhang; Tingting Tian (SAGE Open)
In agricultural production, the unpredictability of crop yields often places farmers under significant financial strain. Banks, constrained by limited credit guarantees and high production risks, are hesitant to offer loans, which severely limits agricultural development. The application of blockchain technology can reduce fraud, information asymmetry, and default risks, thereby enhancing trust and increasing the willingness of banks to provide loans. This study examines the impact of blockchain technology on supply chain coordination and decision-making among members, focusing on agricultural supply chains under centralized and decentralized decision-making frameworks. A comparative analysis of the optimal decisions for farmers and sellers reveals that decentralized decision-making fails to achieve Pareto optimality. To address this, the study introduces cost-sharing contract and cost-sharing-revenue-sharing contract to achieve supply chain coordination. The results indicate that cost-sharing contract cannot achieve coordination, whereas cost-sharing-revenue-sharing contract can bring the supply chain into a coordinated state within a specific range of revenue-sharing coefficient between farmers and sellers. Therefore, the application of blockchain technology not only addresses farmers’ financial constraints but also facilitates supply chain coordination through the use of cost-sharing-revenue-sharing contract.